Effective of education on quality of life and constipation severity in patients with primary constipation - Ozturk, Mehmet Hayrullah; Kilic, Serap Parlar (Elsevier Ireland Ltd, 2019)
Objective: This study was conducted to examine the effect of education on quality of life and constipation severity in patients with primary constipation. Methods: This randomised controlled study was conducted with 80 patients who applied at the gastroenterology outpatient clinic of a university hospital. In the study, the Constipation Questionnaire, Constipation Quality-of-Life Questionnaire (PAC-QOL), and Constipation Severity Instrument (CSI) were used. Results: It was that found after 4 weeks of education, the total PAC-QOL mean score decreased to 60.85 +/- 5.65 and total CSI mean score decreased to 20.17 +/- 4.05 in the intervention group (p < 0.001). No change was observed in the patients in the control group (p > 0.05). After 4 weeks, a statistical difference was found between the two groups in PAC-QOL mean score and CSI mean score (p < 0.05). Conclusion: It was determined that the education given to individuals with primary constipation decreased the constipation severity and increased the quality of life. Practice implications: Constipation education will make a contribution to the active use of follow-up forms by nurses in the clinic for the diagnosis of constipation, individual assessment of each patient, and their active role in constipation management. (C) 2018 Published by Elsevier B.V.
Keywords: Constipation severity; Education; Primary constipation; Quality of life